(untitled) (Global Journal of Medical Research, 2021)
Background: Acute lymphoblastic leukemia (ALL) develops rapidly, creating immature white blood cells (WBCs) called lymphoblasts. This type of hematological malignancy is cancer involving blood and bone marrow (BM). It can affect both B and T cell lineage. Here we studied T